Time-resolved relaxation and cage opening in diamondoids following XUV ultrafast ionization. Issue 48 (6th December 2021) - Boyer, Alexie; Hervé, Marius; Scognamiglio, Audrey; Loriot, Vincent; Lépine, Franck
Abstract : Ultrafast vibrational dynamics induced by XUV excitation was investigated in diamondoids using HHG light source. Abstract : Unraveling ultrafast processes induced by energetic radiation is compulsory to understand the evolution of molecules under extreme excitation conditions. To describe these photo-induced processes, one needs to perform time-resolved experiments to follow in real time the dynamics induced by the absorption of light. Recent experiments have demonstrated that ultrafast dynamics on few tens of femtoseconds are expected in such situations and a very challenging task is to identify the role played by electronic and nuclear degrees of freedom, charge, energy flows and structural rearrangements. Here, we performed time-resolved XUV-IR experiments on diamondoids carbon cages, in order to decipher the processes following XUV ionization. We show that the dynamics is driven by two timescales, the first one is associated to electronic relaxation and the second one is identified as the redistribution of vibrational energy along the accessible modes, prior to the cage opening that is involved in all fragmentation mechanisms in this family of molecules.